2014
DOI: 10.1007/s10488-014-0548-2
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Therapist Self-Report Ratings of Fidelity to Evidence-Based Practices for Adolescent Behavior Problems: Correspondence between Therapists and Observers

Abstract: Developing therapist-report fidelity tools to support quality delivery of evidence-based practices in usual care is a top priority for implementation science. This study tested the reliability and accuracy of two groups of community therapists who reported on their use of family therapy (FT) and motivational interviewing/cognitive-behavioral therapy (MI/CBT) interventions during routine treatment of inner-city adolescents with conduct and substance use problems. Study cases (n = 45) were randomized into two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 60 publications
8
89
0
Order By: Relevance
“…Specifically, an earlier study with the current sample (Hogue, Dauber, Lichvar, et al, 2015) found that UC-FT therapists reported a significantly higher mean level of FT techniques (M = 2.4; SD = .63) than did observational coders (M = 2.0; SD = .45) for the same set of sessions, thereby inflating their scores by an average of four-tenths of a scale point. This simple algebraic adjustment has the virtue of transparency, though it can be applied only to samples that have both therapist- and observer-report fidelity data on a common metric.…”
Section: Methodsmentioning
confidence: 70%
See 4 more Smart Citations
“…Specifically, an earlier study with the current sample (Hogue, Dauber, Lichvar, et al, 2015) found that UC-FT therapists reported a significantly higher mean level of FT techniques (M = 2.4; SD = .63) than did observational coders (M = 2.0; SD = .45) for the same set of sessions, thereby inflating their scores by an average of four-tenths of a scale point. This simple algebraic adjustment has the virtue of transparency, though it can be applied only to samples that have both therapist- and observer-report fidelity data on a common metric.…”
Section: Methodsmentioning
confidence: 70%
“…Therapist-report measures can also enrich routine QA via feedback loops of several kinds, as exemplified in the current study: as a self-check by therapists to mark their own progress in treating cases; a supervision aid for trainers to monitor fidelity; and administrative data for reviewers to evaluate therapist- and agency-level performance (Schoenwald, Letourneau, & Halliday-Boykins, 2005). A previous study documented that the UC-FT therapists in the current sample were reliable in reporting on their own adherence to core FT techniques (Hogue, Dauber, Lichvar, Bobek, & Henderson, 2015; see Fidelity Measure in Method section).…”
Section: Study Background and Innovationsmentioning
confidence: 77%
See 3 more Smart Citations